A unidade de conservação em faixa de fronteira : o revés das concepções - Hoshi, Simone Shizue da Costa (2013)
The work focuses on the conservation area along the border, trying to get the conceptions of the border strip and about conservation, so as to analyze how the concepts involve in speeches from public agencies and the impact that the implementation of public policies engendered by State. The design of the boundary zone has undergone over time indentation and resilience in spite of its width. The understanding being arranged as security or defense was climbing in history, resulting in policies that space, often under the mantle of political and economic expediency. Inaugurated the understanding of said strip the Constitution of 1891, and subsequent, according to the politics of the time change, the understanding has been changing too, until the advent of the 1988 Constitution from which it established the concept of the frontier as well as its width estimated at up to 150 km. The conception of nature protection just falling on two segments or chains: the conservationist and preservationist pure. This is analyzed by the fact that the transplanted model of conservation units in Brazil, much sat on the American model, wide spaces for enjoyment and ideals of pristine landscape. The conservation unit confronts the theory of quickening the borders of geopolitical, since it promotes or attempts to promote the population density for the border strip as an instrument of containment and defense of the territory at the same time. The unit of integral protection confronts such a situation, since one of its prerogatives lies in isolating the area and the exclusion of human presence inside the unit. The unit promotes sustainable use obstacles as well, since these spaces congregate populations, in alliance with the permanence of natural resources conservation practices, but that does not always indicate the conservation of the natural environment. With Decree n. 4411, 2002, authorizing the installation of the Armed Forces and Federal Police in the conservation unit, where they meet the regulatory provisions, re-engaging the design of conservation unit and its goals with the defense of the territory through its installation in the unit, in addition to condition the management plan prior consent to, and participation in its elaboration. This time there is an intricate and interwoven set of discourses and state conservationists.